The Sound Horeg Phenomenon From the Perspective of Pancasila Values on Social Order in Jember Regency - Bella Safira Rachmatika; Helda Mega Maya; Ahmad Fadli (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the phenomenon of sound horeg as a form of the development of public entertainment in Jember across various social activities. The sound horeg phenomenon has positive impacts by strengthening social interaction and creating economic opportunities for local communities. However, it also generates negative consequences, including excessive noise pollution and the potential disruption of public order. The differing public responses to the sound horeg phenomenon indicate a shift in societal values. Therefore, this study aims to understand the sound horeg phenomenon from the perspective of Pancasila values, particularly the second, third, and fourth principles, and its impact on social order within the community. This study employs a descriptive qualitative research method conducted in Jember Regency. Data were collected through observation, semi-structured interviews, and documentation. The data were analyzed using the stages of data reduction, data presentation, and conclusion drawing, while the validity of the findings was ensured through source triangulation. The findings reveal that the sound horeg phenomenon serves not only as a form of public entertainment but also influences people's social behavior in maintaining social order. From the perspective of Pancasila values, the sound horeg phenomenon reflects the values of unity, togetherness, and social justice when it is managed wisely. Conversely, if sound horeg activities are not conducted responsibly, they have the potential to conflict with the values of Pancasila in community life.